EARNING MANAGEMENT AND LEVERAGE AS FACTORS AFFECTING TAX AVOIDANCE MODERATED BY POLITICAL CONNECTIONS - Hariyanto, Jessenia Lorreta; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2025)
Taxpayers face a dilemma because taxes are an obligation and a burden, while the state is very dependent on them. This is based on a sense of injustice for those who do not pay taxes but still enjoy the same facilities. As a result, Indonesian taxpayers have begun to avoid taxes, which has caused the country to lose quite a large amount. In fact, not only do individual taxpayers avoid taxes, but corporate taxpayers also do so. This study uses earnings management and leverage variables as independent variables, political connection variables as moderating variables, and tax avoidance variables as dependent variables. This study focuses on taxpayers who are business entities or companies. Data was taken from the non-cyclical sector companies report of financial published on the IDX in 2020-2023. One hundred seventeen samples were used in this study. SPSS 25 is used as a sample processing tool, and the results obtained are that tax avoidance is significantly influenced by leverage, while earnings management does not have a significant effect on it. The results of this study also show that political connections cannot moderate the influence of the two independent variables on tax avoidance.